(3GdeWdH aj GdYed HGdQHY GdeLjHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi JbOS ai LeGd UaGJg YeG jNWQ ai GdGhgGe CeG HYO aGfg jbhd GdYHO GdabjQ GYde Gfg djS ai GdGdGJ GdadcjI GTQa ef GdQHY GdeLjH s
(3BNQgG (B:s
(3MGd chf GdTeS Ydjg hdG JNai eWGdY GdZQhH heWGdY WdhY GdchcH heZjHg hGdMeO ddg GdPj gh aGJMI cd NWGH JeJ GdQSGdI GdeHGQcI hGdMeO ddg QH GdYGdejf s
(3HChdgG Jedcs
(3HgG fXGe GdJYbjHIs
(3YdjgG ELGRI ef GdeDda dfhQ GdOjf Ydi Hf MSf GdeYQha HGdHMWjWi SfI (B861s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B54 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B188s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1719s
Keywords: (3Gdadcs